Modulation of Heavy Metal/Ferromagnetic Metal Interface for High‐Performance Spintronic Devices. (5th June 2019) - Peng, Shouzhong; Zhu, Daoqian; Zhou, Jiaqi; Zhang, Boyu; Cao, Anni; Wang, Mengxing; Cai, Wenlong; Cao, Kaihua; Zhao, Weisheng
Abstract: Spintronic devices such as magnetic tunnel junctions and skyrmions have attracted considerable attention due to features such as nonvolatility, high scalability, low power, and high speed. Over the past few years, innovative materials and new structures in this field have resulted in the emergence of new phenomena and exciting device performance. It has been found that the heavy metal (HM)/ferromagnetic metal (FM) interface plays an essential role in spintronic devices. Spintronic device performance can be significantly enhanced through proper modulation of this interface. Recent progress in this blooming field is reviewed with specific emphasis on the HM/FM interface. Investigations into HM/FM‐interface‐related phenomena, including perpendicular magnetic anisotropy, tunnel magnetoresistance, magnetic damping, spin–orbit torque, and Dzyaloshinskii–Moriya interaction, are put into context. Guidelines for realizing high‐performance spintronic devices are provided, and an outlook on their future research direction and potential applications is given. Abstract : Innovative materials and new structures for spintronic devices have resulted in the emergence of new phenomena and exciting device performance in recent years. Progress in this field is reviewed, with specific emphasis on the modulation of the heavy metal–ferromagnetic metal interface for high‐performance spintronic devices.